Uji Lapang Campuran Filtrat Kunyit, Jahe dan Lengkuas untuk Pengendalian Penyakit Antraknosa Pada Cabai Rawit Varietas Hiyung - Santi Suminar; Mariana Mariana; Salamiah Salamiah (www.ulm.ac.id, 2022)
ABSTRACT The hiyung variety of cayenne pepper around the swamp area which is now being developed in Hiyung Village. The main problem of chili plants is anthracnose disease caused by the fungus Colletotrichum sp. Anthracnose disease causes the fruit to rot and eventually cause losses so that production will decrease. There are still a lot of use of chemical pesticides to control anthracnose disease, which in excess can have a negative impact on consumers, ecosystems and the environment. To reduce this impact, it is necessary to control cheap, environmentally friendly and safe, namely by using botanical pesticides. This study aims to determine the effect of the concentration of the mixture of turmeric, ginger and galangal filtrate on the incidence of anthracnose. The study used a completely randomized design (CRD) consisting of 4 treatments and 5 replications so that there were 20 experimental units. Chili is grown in Hiyung village, a chili swamp area in South Kalimantan. Anthracnose pathogen inoculation occurs naturally because the area is endemic for anthracnose disease. Application of the test filtrate mixture was carried out when the plants began to flower. The treatment was the concentration of the mixture of turmeric galangal filtrate in water, namely 150 ml/l, 100 ml/l and 50 ml/l. The study showed that the results of the administration of a mixture of turmeric, ginger and galangal filtrate could reduce the anthracnose disease of cayenne pepper hiyung in Hiyung Village. Application of a mixture of turmeric ginger galangal filtrate did not affect the number of fruits, fruit weight and plant height of cayenne pepper hiyung.